Kaposi sarcoma risk in HIV-infected children and adolescents on combination antiretroviral therapy from sub-Saharan Africa, Europe, and Asia - Eliane Rohner (2018)
© The Author 2016. Published by Oxford University Press for the Infectious Diseases Society of America. All rights reserved. Background. The burden of Kaposi sarcoma (KS) in human immunodeficiency virus (HIV)-infected children and adolescents on combination antiretroviral therapy (cART) has not been compared globally. Methods. We analyzed cohort data from the International Epidemiologic Databases to Evaluate AIDS and the Collaboration of Observational HIV Epidemiological Research in Europe.We included HIV-infected children aged <16 years at cART initiation from 1996 onward. We used Cox models to calculate hazard ratios (HRs), adjusted for region and origin, sex, cART start year, age, and HIV/AIDS stage at cART initiation. Results. We included 24 991 children from eastern Africa, southern Africa, Europe and Asia; 26 developed KS after starting cART. Incidence rates per 100 000 person-years (PYs) were 86 in eastern Africa (95% confidence interval [CI], 55-133), 11 in southern Africa (95% CI, 4-35), and 81 (95% CI, 26-252) in children of sub-Saharan African (SSA) origin in Europe. The KS incidence rates were 0/100 000 PYs in children of non-SSA origin in Europe (95% CI, 0-50) and in Asia (95% CI, 0-27). KS risk was lower in girls than in boys (adjusted HR [aHR], 0.3; 95% CI, .1-.9) and increased with age (10-15 vs 0-4 years; aHR, 3.4; 95% CI, 1.2-10.1) and advanced HIV/AIDS stage (CDC stage C vs A/B; aHR, 2.4; 95% CI, .8-7.3) at cART initiation. Conclusions. HIV-infected children from SSA but not those from other regions, have a high risk of developing KS after cART initiation. Early cART initiation in these children might reduce KS risk.